2017
DOI: 10.1186/s40781-017-0128-6
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear modelling to describe lactation curve in Gir crossbred cows

Abstract: BackgroundThe modelling of lactation curve provides guidelines in formulating farm managerial practices in dairy cows. The aim of the present study was to determine the suitable non-linear model which most accurately fitted to lactation curves of five lactations in 134 Gir crossbred cows reared in Research-Cum-Development Project (RCDP) on Cattle farm, MPKV (Maharashtra). Four models viz. gamma-type function, quadratic model, mixed log function and Wilmink model were fitted to each lactation separately and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 15 publications
7
9
0
Order By: Relevance
“…However, WD nlin indicated the best fit for 1/2H, 3/4H, 7/8H and H groups. Torshizi et al (2011) and Bangar and Verma (2017), using similar criteria, reported the superiority of the non-linear Wood's model compared to Wood's linear model when fitting test day milk yield records of Holstein and Gyr breeds, respectively. In fact, Wood's model in the non-linear form has been considered one of the best and most popular functions to describe the lactation curve in dairy cattle (Macciotta et al 2011).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, WD nlin indicated the best fit for 1/2H, 3/4H, 7/8H and H groups. Torshizi et al (2011) and Bangar and Verma (2017), using similar criteria, reported the superiority of the non-linear Wood's model compared to Wood's linear model when fitting test day milk yield records of Holstein and Gyr breeds, respectively. In fact, Wood's model in the non-linear form has been considered one of the best and most popular functions to describe the lactation curve in dairy cattle (Macciotta et al 2011).…”
Section: Discussionmentioning
confidence: 96%
“…The individual performance of animals with different genetic compositions will depend on the prediction of the shape of the lactation curve (Pereira et al 2016). The pattern of the lactation curve is very important in the study of dairy cattle (Bangar and Verma 2017). In general, the common pattern of lactation curves is that milk yield increases in the early stage of lactation reaches a peak yield and then decreases slowly until the end of lactation (Chang et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Genomic prediction of lactation curves represents the genetic behavior of the milk production of the animals in the herd throughout lactation. According to Bangar and Verma (2017), the lactation curve cannot be fitted through a linear model, since its trend is not linear with time. Therefore, several mathematical models have been applied to explain the flow of milk production throughout lactation in dairy cows (Macciotta et al, 2011;Bangar and Verma, 2017;Piccardi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Studies addressing the construction of lactation curves for dairy cattle usually aim to identify the lactation behavior of the herds (Bangar and Verma, 2017) and/or to evaluate the genetic parameters for the lactation traits under study (Macciotta et al, 2015). These approaches are important for characterizing the milk productivity of the herd and for assisting the choice of the equation that best describes its behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the factors mentioned previously, we believe that those variations occurred when cows presented the peak milk yield on the day of parturition or nearly after parturition. These types of lactation profiles occurred for groups BPO 41 and BPO 43 , which might be associated with the poor dairy temperament of Zebu breeds and its crossbreeds with dairy breeds (Bangar and Verma, 2017). Sometimes, even cows that exhibited a typical convex-shaped lactation profile in a previous lactation fail to present a peak milk yield in a further lactation, because of environmental factors such as metabolic disorders, mastitis, other diseases, and nutritional or other management errors (Wood, 1968(Wood, , 1970(Wood, , 1972(Wood, , 1976(Wood, , 1980Macciotta et al, 2005;Hossein-Zadeh, 2016;Ahmed et al, 2019).…”
mentioning
confidence: 99%